Influence of Splitter Angle Variations on the Efficiency and Power of Pelton Turbine - Duma, Gerard Antonini; Sule, Luther; Indah, Andi Besse Riyani; Baru, Cristian (Mekanika: Majalah Ilmiah Mekanika, 2026)
The Pelton turbine is a type of impulse turbine engineered to exploit the potential energy of high-pressure, low-flow water. A pivotal component of the Pelton turbine bucket is the splitter, which serves as a separator at the core of the bucket, bifurcating the water-jet flow into two symmetrical segments. The splitter modulates the distribution and trajectory of the water flow after it impacts the bucket surface. This study examined the effects of splitter-angle variations on the efficiency and power of a Pelton turbine. The turbine was designed with 20 ABS blades fabricated using 3D printing technology and assessed under splitter-angle configurations of 15°, 25°, 50°, 75°, 100°, and 125°, as well as in the absence of a splitter. Four discharges (0.000692; 0.000663; 0.000642 and 0.000623 m³/s) and various loads, starting from 0.2 to 3.0 kg, with a range of 0.2, were tested. The findings indicate that the splitter angle profoundly affects turbine efficiency, with the 50° angle producing the highest efficiency and power of 89% and 24 W, respectively, at a load of 2.0 kg, a turbine rotation of 285 rpm, and a torque of 0.8044 Nm, with a discharge of 0.000692 m³/s. The experimental and simulation results emphasize the importance of optimizing the splitter geometry to improve energy conversion efficiency and overall turbine performance.